Evaluation of technology‐based learning by dental students during the pandemic outbreak of coronavirus disease 2019. (6th September 2020) - Al‐Taweel, Firas B.; Abdulkareem, Ali A.; Gul, Sarhang S.; Alshami, Muhanad L.
Abstract: Introduction: Although technology‐based learning (TB learning) has been accepted as an efficient educational tool in the field of dentistry, the evaluation of TB learning in non‐prepared situations such as pandemics has not been fully investigated. This study aimed to evaluate different aspects of TB learning amongst undergraduate dental students during the pandemic outbreak of COVID‐19. Materials and Methods: Dental students in selected Iraqi universities (University of Baghdad, University of Sulaimani and Dijlah University College) were invited to join the study. A questionnaire was created using a Google platform and answered by students. Satisfaction and attitude towards TB learning plus total evaluation scores for lecturers were examined. Results: A total of 832 out of 1800 dental students participated in the study. The majority of participants have basic (40.7%) and intermediate (47.5%) computer skills, and more than half of them lack any experience in TB learning. The overall satisfaction and positive attitude towards TB learning were less than 50%. Students at final grade, with advanced computer skills and TB learning experience, showed higher satisfaction (OR: 3.031, 2.876, 3.644, respectively) and a more positive attitude (OR: 3.172, 3.035, 3.477, respectively) towards TB learning than those at earlier grades. Total evaluation scores for lecturers were higher amongst females (11.5 ± 5.8) than males (9.9 ± 7.2) as well as amongst participants at final grade (14.0 ± 6.2), with advanced computer skills (13.8 ± 6.1) and TB learning experience (16.2 ± 6.0). Conclusions: Dental students demonstrated low‐moderate satisfaction and positive attitude towards TB learning and the quality of material presented to them. Integrating TB learning into the dental education curriculum is an essential step in enhancing the acceptance of TB learning in the future.